2018
DOI: 10.1080/17515831.2018.1531651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sodium octanoate on the tribocorrosion behaviour of 5052 aluminium alloy

Abstract: The 5000 series aluminium alloys are commonly used in a marine application where it is exposed to environments containing the chloride ions, which cause corrosion of aluminium alloy. The situation becomes even worse when aluminium alloys, in some situations, may suffer from combined corrosion and wear actions. The present study has been carried out to investigate the effect of sodium octanoate as a corrosion inhibitor on the corrosive wear behaviour of aluminium alloy 5052 in 0.5 M NaCl solution as simulated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Therefore, the inhibitor molecules may have modified the electrochemical activity at the bottom of the pit, inhibiting electrochemical reactions that can occur within the pit. Finally, in some studies (Hong et al , 2016; Zhao et al , 2018), it has been reported that a higher concentration of inhibitor can cause pitting corrosion. In the present case of the Gemini surfactant, it can be explained by the desorption of inhibitor molecules and the formation of aggregated micelles in the solution when the concentration is far above the CMC.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the inhibitor molecules may have modified the electrochemical activity at the bottom of the pit, inhibiting electrochemical reactions that can occur within the pit. Finally, in some studies (Hong et al , 2016; Zhao et al , 2018), it has been reported that a higher concentration of inhibitor can cause pitting corrosion. In the present case of the Gemini surfactant, it can be explained by the desorption of inhibitor molecules and the formation of aggregated micelles in the solution when the concentration is far above the CMC.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The corrosion testing parameters, such as applied current/potential [56], corrosion inhibitor [57,58], and electrolyte composition [59,60]; and (3) The wear testing parameters, such as applied load [59,61] and speed [61,62]. For the material parameter effects, Ferreira et al [50] investigated the effects of spatial distribution of reinforcing particles (e.g., Al 3 Ti and Al 3 Zr) on the tribocorrosion resistance of Al-5 wt.% Ti and Al-5 wt.% Zr in 0.6 M NaCl solution.…”
Section: Brief History and Literature Survey From The Past Five Decadesmentioning
confidence: 99%
“…Specifically, as shown in Figure 2a, the pure wear loss (V M0 in Figure 2a) remained relatively constant, while V C , the total material loss caused by pure corrosion, and ∆V M , the corrosioninduced wear, became increasingly larger at the more anodic potentials. The presence of corrosion inhibitor [57,58] and electrolyte composition [59,60] also affects the overall tribocorrosion rate. Corrosion inhibitors such as sodium octanoate [57] and zinc phosphate [58] were found to reduce tribocorrosion rate of Al alloys in NaCl solutions due to the formation of a surface barrier that not only limit mass and charge transfer to reduce corrosion, but also lowers surface friction to reduce wear.…”
Section: Brief History and Literature Survey From The Past Five Decadesmentioning
confidence: 99%
See 1 more Smart Citation